2022
DOI: 10.1111/jre.13049
|View full text |Cite
|
Sign up to set email alerts
|

Smoking negatively impacts the clinical, microbiological, and immunological treatment response of young adults with Grade C periodontitis

Abstract: Objective This study aimed to investigate the influence of smoking on clinical, microbiological and immunological parameters in young adult with stage III‐IV Grade C periodontitis after full‐mouth ultrasonic debridement (FMUD) associated with Amoxicillin and Metronidazole (AMX + MTZ), comparing smokers (PerioC‐Y‐Smk) with non‐smokers (PerioC‐Y‐NSmk). Materials and Methods Fifteen PerioC‐Y‐NSmk and 14 PerioC‐Y‐Smk patients underwent FMUD associated with AMX + MTZ for 10 days. All parameters were collected at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In our study, we observed that smoking was associated with decreased levels of all biomarkers in GCF. This finding contradicts some existing literature which suggests that smoking actually increases TNF‐α expression 44–46 . However, Fredrikson et al conducted a study in which they did not find a statistically significant difference in TNF‐α levels released in response to bacterial stimulation between smoking and non‐smoking groups 47 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our study, we observed that smoking was associated with decreased levels of all biomarkers in GCF. This finding contradicts some existing literature which suggests that smoking actually increases TNF‐α expression 44–46 . However, Fredrikson et al conducted a study in which they did not find a statistically significant difference in TNF‐α levels released in response to bacterial stimulation between smoking and non‐smoking groups 47 .…”
Section: Discussionmentioning
confidence: 80%
“…This finding contradicts some existing literature which suggests that smoking actually increases TNFα expression. [44][45][46] However, Fredrikson et al conducted a study in which they did not find a statistically significant difference in TNFα levels released in response to bacterial stimulation between smoking and non-smoking groups. 47 They attributed this to the low sensitivity of peripheral lymphocytes to stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk identified factors were "gums bleeding" and "low bone density" [37,38]. Compared to non-smokers, smoking tobacco caused greater gingival recession and gingival pocket depths and a decrease in tissue repair and immune response [39].…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, smoking and being overweight or obese were identified as significant risk factors associated with periodontitis in younger adults. Da Silva et al [39] examined the influence of smoking on periodontal health and inflammatory markers in patients who received full-mouth ultrasonic debridement coupled with the use of amoxicillin and metronidazole. Their findings revealed a significant association between smoking and higher probing depth, bleeding on probing, and gingival recession compared to nonsmokers after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation